2016
DOI: 10.1002/hbm.23436
|View full text |Cite
|
Sign up to set email alerts
|

The effects of HIV and aging on subcortical shape alterations: A 3D morphometric study

Abstract: Standard volumetric neuroimaging studies have demonstrated preferential atrophy of subcortical structures among individuals with HIV. However, to our knowledge, no study has investigated subcortical shape alterations secondary to HIV and whether advancing age impacts that relationship. This study employed 3D morphometry to examine the independent and interactive effects of HIV and age on shape differences in nucleus accumbens, amygdala, caudate, hippocampus, pallidum, putamen and thalamus in 81 participants ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 95 publications
3
23
4
Order By: Relevance
“…25 For episodic memory, the neuroanatomical referent is the hippocampus, wherein dysfunction and atrophy have been noted to occur independently with both aging 26 and HIV infection 27 as well as in a deleterious interaction between aging and HIV infection. 28 Several studies have documented these regions to be of particular concern for damage in the setting of older persons with HIV infection. A critical review reported that HIV infection has been associated with greater than age-related brain atrophy in the basal ganglia and hippocampus.…”
Section: Discussionmentioning
confidence: 99%
“…25 For episodic memory, the neuroanatomical referent is the hippocampus, wherein dysfunction and atrophy have been noted to occur independently with both aging 26 and HIV infection 27 as well as in a deleterious interaction between aging and HIV infection. 28 Several studies have documented these regions to be of particular concern for damage in the setting of older persons with HIV infection. A critical review reported that HIV infection has been associated with greater than age-related brain atrophy in the basal ganglia and hippocampus.…”
Section: Discussionmentioning
confidence: 99%
“…However, the literature disagrees on whether there is an interactive relationship between HIV infection and aging in cognitively unimpaired patients (Holt, Kraft-Terry, & Chang, 2012). Some scientists contend that there is no interactive or synergistic effect of HIV and aging on the brain Valcour et al, 2004a), whereas others contend that HIV infection accelerates brain aging (Kuhn et al, 2016;Morgan, Lee, & Nyagode, 2011;Sacktor et al, 2010;Vance, McGuinness, Musgrove, Orel, & Fazeli, 2011). We suggest here that the previous inability to detect significant Age*HIV interactive effects in WM microstructure may be due to methodological differences (including neuroimage processing, statistical analysis, and sample size) rather than the lack of an Age*HIV interaction.…”
Section: Introductionmentioning
confidence: 99%
“…Although no significant relationships between BAG and nadir CD4+ or HIV disease duration were reported, the authors investigated white matter volume, rather than white matter microstructure (using DTI) and in a sample of HIV+ participants with undetectable viral loads. Thus, it is unclear to which degree findings of "attenuated brain aging" in HIV 9,11,12 may be mediated by primary or secondary processes related to the infection. It is also unclear what effects these processes may have on WM microstructure.…”
Section: Introductionmentioning
confidence: 99%